Management of castration-resistant prostate cancer: bisphosphonates and emerging therapies. Issue 12 (December 2010) - Saad, Fred; Colombel, Marc
Approximately 70% of patients with prostate cancer will develop bone metastases that often lead to bone pain and skeletal-related events. Several bisphosphonates have shown promising activity for palliating pain. Only zoledronic acid has significantly delayed the onset and reduced the incidence of skeletal-related events in men with castration-resistant prostate cancer. In addition, studies suggest that bisphosphonates have anticancer activity that may prevent disease progression and improve survival. Clodronate was shown to improve survival in a study of men with metastatic androgen-sensitive prostate cancer. Emerging therapies are being investigated for their ability to maintain bone health. The findings presented herein highlight the importance of bone-targeted therapies for patients with bone metastases from prostate cancer.